Novel Autosomal Recessive c10orf2 Mutations Causing Infantile-Onset Spinocerebellar Ataxia - Jessica N. Hartley; Frances A. Booth; Marc R. Del Bigio; Aizeddin A. Mhanni (Hindawi Limited, 2012)
Recessive mutations in genes encoding mitochondrial DNA replication machinery lead to mitochondrial DNA depletion syndromes. This genetically and phenotypically heterogeneous group includes infantile onset spinocerebellar ataxia (OMIM# 271245) a neurodegenerative disease caused by mutations in the mtDNA helicase gene, c10orf2, with an increased frequency in the Finnish population due to a founder mutation. We describe a child of English descent who presented with a severe phenotype of IOSCA as a result of two-novel mutations in the c10orf2 gene. This paper expands the phenotypic spectrum of IOSCA and adds further evidence for the presence of a genotype-phenotype correlation among patients with recessive mutations in this gene.